Distortion compensation technique for high resolution microscopy - Borovytsky, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
The paper represents the technique for distortion compensation in digital images from high resolution optical microscopes. This technique is based on approximation of necessary pixel shifts as a power function that can be identified using small set of data from distorted digital images of diffraction gratings. The experimental studies confirmed efficiency of the proposed technique for decreasing distortion till a level of spatial discretization.